2017
DOI: 10.1002/ccr3.1112
|View full text |Cite
|
Sign up to set email alerts
|

Full mouth rehabilitation with retrievable metal–ceramic implant‐supported fixed prostheses for a young patient with atrophic jaws: a clinical report

Abstract: Key Clinical Message Treatment of atrophic edentulous jaws with implant‐supported fixed prostheses is one of the most complicated challenges in dentistry. This clinical report describes the prosthesis which consists of screw retained frameworks with individual cement retained crowns which combines the advantages of the screw retained restoration with the advantage of cement retained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Other clinicians also successfully applied this strategy. 1,5 In patients with AI, Ameri et al 8 recommended extractions of all unrestorable teeth and rehabilitation with implant-supported prosthesis as the most effective choice, which was also carried out in the present case.…”
Section: Discussionmentioning
confidence: 64%
“…Other clinicians also successfully applied this strategy. 1,5 In patients with AI, Ameri et al 8 recommended extractions of all unrestorable teeth and rehabilitation with implant-supported prosthesis as the most effective choice, which was also carried out in the present case.…”
Section: Discussionmentioning
confidence: 64%
“…The results of the study showed that category II showed the highest number of cases, which is slightly reassuring as they have better prognosis due to available interarch space (Lewis and Smith, 1973;Turner and Missirlian, 1984). Cases Reports by Song et al (Brecker, 1959;Song et al, 2010), Bencharit S et al (Bencharit et al, 2010), Ameri N, (Ameri et al, 2017), Kumar AV et al (Kumar et al, 2012) showed various permutations and combinations of protocols and treatment options for full mouth rehabilitation.…”
Section: Resultsmentioning
confidence: 85%
“…Non-carious tooth surface lesions (NCTSL) are usually classi ied as Abrasion, Attrition, Erosion, and Abfraction (Ameri et al, 2017). There care multiple systemic factors that could exponentially increase the loss of tooth structure.…”
Section: Resultsmentioning
confidence: 99%